Answer:
1. 7*3 - 7*x = -63
2. 3-x = -63/7
Step-by-step explanation:
1. 7(3-x) = -63
7*3 - 7*x = -63
2. 3-x = -63/7
Answer:
9x² - 4/3x + ¼
Step-by-step explanation:
(3x - ½)²
(3x - ½)(3x -½)
9x² - ⅔x - ⅔x + ¼
9x² - 4/3x + ¼
For this you need to know your angles in parallel lines.
3y will equal 87 as they are opposite angles and opposite angles are equal.
So y = 87/3
We can use the knowledge that angles in a straight line (in parallel line diagrams) will add up to 180. Therefore we do 180-87= 93. Now we know 3x=93 because just like the first example they are opposite angles. Now we know x=93/3.
(I didn’t have a calculator on me so you’ll have to work out the final result. Also I recommend looking into angles in parallel lines. I tried my best to explain so I hope you understand the jist of what I was trying to say.)
Answer:
it can be a pain when nobody helps... ur top right is correct
Step-by-step explanation:
heres a screenshot ..